Cerebral cognitive mapping as an alternative for the safe resection of abscessed metastasis secondary to neuroendocrine neoplasm - Canzio, Florencia Luana; Bolko, Alexia; Pinto, Martín; Carballo, Leandro; Echavarría Demichelis, Mickaela (Revista Argentina de Neurocirugía, 2026)
Background: abscessed brain metastases are an extremely rare manifestation of oncological pathologies, particularly in patients with neuroendocrine tumors. Their clinical and radiological presentation can mimic pyogenic abscesses or high-grade gliomas, which affects the differential diagnosis and therapeutic options. The choice of an awake surgical technique with intraoperative multimodal cognitive mapping, traditionally reserved for low-grade gliomas, allowed for oncologically safe resection without generating permanent neurological deficits.Objectives: to describe a case approached using an alternative surgical technique with multimodal cognitive mapping, achieving complete resection without new neurological deficits.Case description: a 66-year-old female patient presented primarily with episodes of disorientation. Magnetic resonance imaging revealed a mesial temporal lesion with central cystic-like areas with perilesional edema and heterogeneous enhancement. A high-grade glial lesion was suspected.Surgery: an awake craniotomy was performed using intraoperative cortical mapping techniques using direct stimulation and cognitive tasks. Critical functional areas were identified, and a complete resection was achieved. Histopathology confirmed metastasis with inflammatory changes and necrosis suggestive of abscessation. A positive finding on upper gastrointestinal video endoscopy revealed cells suggestive of neuroendocrine cancer.Conclusion: awake surgery with cognitive mapping allows for a safe approach to metastatic lesions in eloquent regions, even in complex cases with prior cognitive impairment. This approach represents a valuable tool for optimizing the balance between oncological control and functional preservation.
Keywords: Abscessed metastasis; Cognitive mapping; Neuroendocrine neoplasia; Safe resection